The Geochemical Evolution of Santa Cruz Island, Galápagos Archipelago - Wilson, E. L.; Harpp, K. S.; Schwartz, D. M.; Van Kirk, R. (Frontiers in Earth Science, 2022)
Santa Cruz Island is a dormant shield volcano, centrally located in the Galápagos Archipelago. Exposed lavas preserve more than 1 million years of activity in two eruptive units. The older Platform Series’ activity peaked between ~1620 ± 15 and 1160 ± 35 ka, and is exposed primarily in the northeastern quadrant. The Shield Series blankets the rest of Santa Cruz and was likely erupted from a WNW trending fissure system between 271 ± 17 and 74 ± 38 ka. Platform Series lavas are more evolved and isotopically enriched than Shield lavas, but are neither as compositionally monotonous nor as isotopically enriched as the younger western Galápagos volcanoes. Santa Cruz formed when the Galápagos Spreading Center (GSC) was closer to the plume than it is today, resulting in enhanced plume-ridge interaction and transport of plume material to the ridge. Consequently, the Platform Series was formed under relatively magma-starved conditions compared to the western volcanoes today. Magma supply was sufficient for partial fractionation and homogenization of melts in shallow reservoirs, but inadequate to support thermochemically buffered networks like those in the present-day western archipelago. The slight depletion of Platform Series lavas relative to Fernandina reflects entrainment of depleted upper mantle and/or diversion of deep, enriched plume melts to the nearby GSC. The younger Shield Series lavas are even more depleted because plate motion has carried the volcano across the compositional boundary of the bilaterally asymmetric plume into its more depleted zone. Shield Series lavas’ variable, primitive compositions reflect minimal crustal processing in small, ephemeral, poorly supplied magma reservoirs. Unlike the young western shields, the constructional history of Santa Cruz has been controlled to a significant extent by its proximity to the GSC.